Congenital hepatic hemangioma presenting with neonatal intestinal obstruction: A case report - Sumaira Noor Maham; Shabbir Ahmad; Muhammad Jawad Afzal; Nabila Talat (EL-Med-Pub, 2021)
Background: Congenital hepatic hemangioma usually presents with abdominal distension. Rarely it may cause intestinal obstruction. We present a case of congenital hepatic hemangioma causing neonatal intestinal obstruction. Case Presentation: A 4-day-old neonate presented with clinical and radiological features of neonatal intestinal obstruction. On exploration, a loop of jejunum was found adherent with a hepatic mass, arising from the left lobe of the liver. The hepatic mass profusely bled in an attempt of removing the adherent jejunal loop. Thus, the adherent portion was isolated and jejunojejunal end to end anastomosis was done. The hepatic mass along with an adherent small piece of jejunum was also excised. Histopathology showed hepatic hemangioma. The patient is doing fine on the 10-month follow-up. Conclusion: We report a rare presentation of congenital hepatic hemangioma with neonatal intestinal obstruction. Although the optimum therapy for hepatic hemangioma is medical management, at times, surgical resection becomes a necessary option.